Vernacular Digital Games as English Language Learning Tools: An Exploratory Study in the Syrian Context - Dayoub , Dima (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The popularity of Vernacular or Commercial-off-the-Shelf games in Syria is a given. This research is the first step to harness and utilize the affordances of such games in English language learning. To this end, an exploratory questionnaire was devised to collect data about the gaming habits of a group of Syrians and to explore whether digital games are positively perceived as instrumental in the development of English language. It particularly sheds light on the players’ self-reported interactions during and around the game, their progression throughout the game, their opinions about the ideal combination of multimedia elements games should afford. The research finally invites their suggestions as to how to maximize the efficacy of digital games in English language learning. In sum, participants particularly stressed the importance of structuring spaces for language use as precondition to progressing in a vernacular game, without compromising the entertainment that characterizes such game genre.